Estudo da incubação da canforquinona e do fujenal com fungos como modelo para biotransformação de terpenos - Giovanni Gontijo de Souza (2008)
Biotransformations are a useful tool of great applicability either in basic as in applied research. They can be accomplished by using whole cells of microorganisms, plant and animals or using enzymes isolated from them. In the present work, fungal biotransformations of camphorquinone and fujenal were studied. Initially the biotransformation of camphorquinone, a bicyclic monoterpene, was screened using the fungal species Mucor plumbeus, Thamnostylum sp., Lecanicillium muscarium e Syncephalastrum racemosum. Reactions were carried out by 5, 10, 15 and 20 days and the products were analyzed by gas chromatography coupled to mass spectroscopy (GCMS). Three products were detected when M. plumbeus was used although small amounts of mphorquinone were detected in its unaltered form. One of the products showed to be a monoketo-alcohol that was detected all over the reaction period. Using Thamnostylum sp., two products were detected; the first one only after 10 days of reaction and, the second one, after 10, 15 and 20 days of reaction.From the experiment using Lecanicillium muscarium there were detectedfour products, one of them, observed after 15 days of reaction, showed to be a monoketo-alcohol. Using Syncephalastrum racemosum no products were detected. Analysis of the controls indicated that camphorquinone is stable in the biotransformations conditions and therefore, detected products are not fungal metabolites but correspond to camphorquinone fungal metabolization. A theoretical study was simultaneously conducted towards the most common onoketo-alcohols reported in the literature from camphorquinone biotransformation. It was observed that, in theory, (-)-3S-endo-hydroxyepicamfor should be the most abundant monoketo-alcohol present in solution, in agreementwith the most common data found in the literature. From the reaction of fujenal with the fungus Thamnostylum sp., two biotransformation roducts were isolated by silica gel column chromatography. However, analysis of 1H and 13C NMR spectra of such products was not completely unambiguous. There were observed strong spectral evidences that one of the products is a fujenal glucoside.